2016
DOI: 10.3847/0004-637x/826/2/104
|View full text |Cite
|
Sign up to set email alerts
|

The Panchromatic Hubble Andromeda Treasury. Xv. The Beast: Bayesian Extinction and Stellar Tool*

Abstract: We present the Bayesian Extinction And Stellar Tool (BEAST), a probabilistic approach to modeling the dust extinguished photometric spectral energy distribution of an individual star while accounting for observational uncertainties common to large resolved star surveys. Given a set of photometric measurements and an observational uncertainty model, the BEAST infers the physical properties of the stellar source using stellar evolution and atmosphere models and constrains the line of sight extinction using a new… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 67 publications
(105 reference statements)
2
81
0
Order By: Relevance
“…We note that there is a unique HST blue source in the 0 4 region (the open blue star in Figure 6). Fitting the 4-band spectral energy distribution (SED) using the Bayesian Extinction and Stellar Tool (Gordon et al 2016) suggests that it is not consistent with any model of stable evolutionary phases, suggesting that it is a post-AGB and/or the X-ray source is contaminating the UV and optical flux. We examined the F275W-F336W color and magnitude of this blue source and found that it is likely a hot post-horizontal branch star at the distance of M31 as studied in Rosenfield et al (2012).…”
Section: Uv and Optical Counterpartsmentioning
confidence: 99%
“…We note that there is a unique HST blue source in the 0 4 region (the open blue star in Figure 6). Fitting the 4-band spectral energy distribution (SED) using the Bayesian Extinction and Stellar Tool (Gordon et al 2016) suggests that it is not consistent with any model of stable evolutionary phases, suggesting that it is a post-AGB and/or the X-ray source is contaminating the UV and optical flux. We examined the F275W-F336W color and magnitude of this blue source and found that it is likely a hot post-horizontal branch star at the distance of M31 as studied in Rosenfield et al (2012).…”
Section: Uv and Optical Counterpartsmentioning
confidence: 99%
“…However, it is possible that these have spatial variation, and this could lead to scatter in the flux ratios. Robust SED fitters, such as the BEAST (Gordon et al 2016) may be able to measure such region-to-region variation. Additionally, scattering of light by dust (Section 4.4) may alter the effective attenuation curve in a given region, producing extra flux that does not originate in that region and giving the attenuation curve a shape that is different from that of a perfectly known extinction curve.…”
Section: Dust Modelsmentioning
confidence: 99%
“…Such fitting, though, ideally produces the star's full spectrum, both reddened and intrinsic, which can then be used to infer the flux at wavelengths that were not observed. The PHAT survey motivated the development of the Bayesian Extinction and Stellar Tool (BEAST; Gordon et al 2016), an SED fitter thatcould be used to provide anindependent check of the results presented in this paper. SED fitting will, however, miss any stars below the detection limit, because it requires that they be detected in multiple filters.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis showed that our broadband exposures covered a short enough portion of the orbit that the thermal expansion and contraction of the optics caused a significant offset between the orbit-averaged PSF used by DOLPHOT and that of the F625W images across epochs, which introduced a systematic error that we further discuss in Appendix A. Next, our source catalog was enhanced by adding the output of the Bayesian Extinction And Stellar Tool (BEAST; Gordon et al 2016a) on the PHAT catalog data, which added T e f f , log g, and age information for each source. Gordon et al (2016a) developed the BEAST to model the observed broad spectral energy distribution (SED) of an individual star by considering the full observational uncertainties.…”
Section: Data Reductionmentioning
confidence: 99%